The Role of System-Specific Molecular Chaperones in the Maturation of Molybdoenzymes in Bacteria - Meina Neumann; Silke Leimkühler (Biochemistry Research International)
Biogenesis of prokaryotic molybdoenzymes is a complex process with the final step representing the insertion of a matured molybdenum cofactor (Moco) into a folded apoenzyme. Usually, specific chaperones of the XdhC family are required for the maturation of molybdoenzymes of the xanthine oxidase family in bacteria. Enzymes of the xanthine oxidase family are characterized to contain an equatorial sulfur ligand at the molybdenum center of Moco. This sulfur ligand is inserted into Moco while bound to the XdhC-like protein and before its insertion into the target enzyme. In addition, enzymes of the xanthine oxidase family bind either the molybdopterin (Mo-MPT) form of Moco or the modified molybdopterin cytosine dinucleotide cofactor (MCD). In both cases, only the matured cofactor is inserted by a proofreading process of XdhC. The roles of these specific XdhC-like chaperones during the biogenesis of enzymes of the xanthine oxidase family in bacteria are described.